2013
DOI: 10.5993/ajhb.37.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Problem Behavior, Victimization, and Soda Intake in High School Students

Abstract: Objective-To examine associations of problem behaviors and victimization with nondiet soda intake among a national sample of 16,188 US high school students.Methods-We used the 2009 national Youth Risk Behavior Survey. The outcome measure was daily nondiet soda intake.Results-Smoking, having any sex partners, not always wearing a seat belt, being bullied/ threatened/injured on school property, and being physically hurt by their boyfriend/girlfriend were significantly associated with daily nondiet soda intake af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Previous studies employing various techniques of data analysis have also shown a similar pattern of clustering for insufficient physical activity and low fruit intake (as part of an unhealthy diet) in adolescents, 11,14,[32][33][34][35] thus characterizing a sedentary lifestyle. As for the first cluster, equivalent findings have been reported, especially concerning the co-occurrence of smoking and drug use, 13 smoking and high sugar intake, 36,37 and less frequent oral and general hygiene practices. 37,38 A study restricted to Saudi Arabian male adolescents has found through HACA In relation to the aforementioned clustering of high sugar intake behaviours and illegal drug use, it is noteworthy that a study identified the neural activity linked to food addiction.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies employing various techniques of data analysis have also shown a similar pattern of clustering for insufficient physical activity and low fruit intake (as part of an unhealthy diet) in adolescents, 11,14,[32][33][34][35] thus characterizing a sedentary lifestyle. As for the first cluster, equivalent findings have been reported, especially concerning the co-occurrence of smoking and drug use, 13 smoking and high sugar intake, 36,37 and less frequent oral and general hygiene practices. 37,38 A study restricted to Saudi Arabian male adolescents has found through HACA In relation to the aforementioned clustering of high sugar intake behaviours and illegal drug use, it is noteworthy that a study identified the neural activity linked to food addiction.…”
Section: Resultsmentioning
confidence: 57%
“…Previous studies employing various techniques of data analysis have also shown a similar pattern of clustering for insufficient physical activity and low fruit intake (as part of an unhealthy diet) in adolescents, thus characterizing a sedentary lifestyle. As for the first cluster, equivalent findings have been reported, especially concerning the co‐occurrence of smoking and drug use, smoking and high sugar intake, and less frequent oral and general hygiene practices …”
Section: Discussionmentioning
confidence: 57%
“…)” Response options included, “I did not drink soda or pop during the past 7 days”, “1–3 times during the past 7 days”, “4–6 times during the past 7 days”, “1 time per day”, “2 times per day”, “3 times per day”, and “4 or more times per day”. For this analysis, a dichotomous response category was created: <1 versus ≥1 time/day to identify frequent regular soda consumers (i.e., daily intake of regular soda) [8,10]. …”
Section: Methodsmentioning
confidence: 99%
“…Frequent (e.g., daily) consumption of SSBs is related to adverse health consequences including but not limited to weight gain/obesity [3], cardiovascular health [4], dental caries [5], asthma [6], poor diet quality [7], and poor academic achievement [8] among children and adolescents. Additionally, daily SSB intake is significantly associated with insulin resistance in adolescents [9], and daily intake of regular soda is significantly associated with problem behaviors and victimization among US high school students [10]. …”
mentioning
confidence: 99%
“…Yet in the latter study the link between energy drink consumption and the substance use outcomes was stronger than for the regular soft drinks. Smoking, being bullied/threatened/injured on school property, and other risk behaviours were significantly associated with daily non-diet soda intake (Park, Blanck, Sherry & Foti, 2013).…”
Section: Sugar Consumption and Risk Behaviourmentioning
confidence: 98%